MULTIFUNCTIONALITY: ENVIRONMENT VERSUS RURAL VIABILITY IN SOCIAL OPTIMA - Markku Ollikainen (한국농촌경제연구원, 2009)
We examine policy implications of including rural viability to the notion of multifunctional agriculture. We assume that rural viability refers predominantly to the number of people living in rural areas to keep the infrastructure and living conditions at good state for a good life. The economic core of viability is employment in agriculture and agriculture serving sectors. Viability benefits are modelled with the help of a viability valuation function. We demonstrate that rural viability entails adjusting fertilizer tax and buffer strip subsidy below their environmental first-best Pigouvian levels to reflect the direct and indirect employment effects of agricultural production. Moreover, when non-agricultural land use is present, an additional, non-agricultural instrument is needed to adjust the amount of land allocated to agriculture to its socially optimal level. Thus, inclusion of rural viability creates distortions in multifunctional policies. Theoretical results are illustrated with Finnish data to examine how the inclusion of rural viability to multifunctionality relates to the true socially optimal agri-environmental multifunctionality. We also assess welfare loss from promoting rural viability in the case where there is no base on viability benefits.
Keywords: biodiversity; employment; nutrient runoff; rural viability; biodiversity; employment; nutrient runoff; rural viability